Mitochonic acid 5 mitigates age-related hearing loss progression by targeting defective 2-methylthiolation in mitochondrial transfer RNAs - Kouga, Teppei; Miwa, Toru; Wei, Fan-yan; Sunami, Kishiko; Tomizawa, Kazuhito (Frontiers in Cellular Neuroscience, 2025)
IntroductionAge-related hearing loss (ARHL) is linked to dementia, with mitochondrial dysfunction playing a key role in its progression. Deficient mitochondrial tRNA modifications impair protein synthesis and energy metabolism, accelerating ARHL. Mitochonic acid 5 (MA-5) has shown promise as a therapeutic candidate by improving mitochondrial function, reducing oxidative stress, and stabilizing membrane potential.MethodsIn this study, we investigated the effects of MA-5 on ARHL in cyclin-dependent kinase 5 regulatory subunit-associated protein 1 (Cdk5rap1) knockout (KO) mice, which exhibit early-onset ARHL due to abnormalities in mitochondrial transfer RNA (mt-tRNA) modifications.ResultsMA-5 treatment effectively attenuated ARHL progression in Cdk5rap1-KO mice by improving auditory brainstem response thresholds and distortion product otoacoustic emissions. It also reduced spiral ganglion and outer hair cell loss, while preserving the cochlear structural integrity by preventing mitochondrial degeneration in spiral ligament fibrocytes. Mechanistically, MA-5 upregulated the expression of silent information regulator sirtuin 1 and promoted the nuclear translocation of yes-associated protein, both of which are involved in regulating mitochondrial function and cellular senescence. Metabolomics analysis further demonstrated that MA-5 restored mitochondrial metabolism, reduced lactate accumulation, and maintained mitochondrial integrity.ConclusionThese findings suggest that MA-5 is a viable treatment option for ARHL and other age-related disorders associated with mitochondrial dysfunction.